Genetic diversity of Capsicum annuum L. in local and imported samples in Iraq by using RAPD-PCR - Ihsan A. Hussein; Shaymaa S. Mahdi; Shaymaa S. Mahdi (Ibn Al-Haitham Journal for Pure and Applied Sciences, 2016)
Genetic variation was studied in 22 local and imported samples collected from local Iraqi market by using random amplified polymorphic DNA (RAPD-PCR). Five randomly primers set were used in this study. These primers produced 292 bands. Molecular weights of these bands ranged between 1.8 Kb (1800 bp) to 150 bp. The percentage of polymorphic bands is 100%, with one distinguished band which is produced by using C52 primer. The other primers did not produce any distinguished band. The results of Dendrogram of the studied samples depended on RAPD-PCR results by using Jaccard coefficient for genetic similarity was distributed the samples into 8 groups. This Dendrogram revealed a higher similarity between Iraqi/Yousifia green bell pepper and Jordanian yellow bell pepper with 0.84 values. This value is the highest between samples in comparison with lowest values (0.0) which are found between Iranian yellow bell pepper and the other samples. There are another high values were revealed between Italian orange and red bell pepper with 0.74 values. Also, other high similarity values revealed between Spanish red bell pepper and Italian green bell pepper with 0.73 values; Iranian red bell pepper and Jordanian green bell pepper with 0.72 values; Iraqi/Souwyera green bell pepper and Iraqi/Yousifia green bell pepper with Jordanian yellow bell pepper (the last two samples in same subgroup) with 0.69 values, and last between Iraqi/Balad green bell pepper and Chinese red bell pepper with 0.61 values. The genetic distance between studied samples by using Euclidean coefficient revealed the highest values between Chinese yellow bell pepper and Iranian green bell pepper with 5.0 values, in comparison with the lowest genetic distance between Spanish green bell pepper and Italian yellow bell pepper with 1.0 value.